2005
DOI: 10.1152/jn.00881.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Neuronal Firing Rates in Pallidal and Cerebellar Receiving Areas of Thalamus in Patients With Parkinson's Disease, Essential Tremor, and Pain

Abstract: The motor symptoms of Parkinson's disease (PD) are thought to result from increased inhibitory outflow from the basal ganglia to the pallidal receiving areas of thalamus (ventral oral anterior and posterior-Voa,Vop). To test this hypothesis, we examined the firing rates of neurons in pallidal and cerebellar receiving areas of thalamus in five PD patients and compared them to those of neurons in comparable regions of motor thalamus in two other patient groups where hyperactivity of GPi is not believed to occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 50 publications
6
71
3
Order By: Relevance
“…These results are consistent with the classical model of the functional basal ganglia circuitry, in which increased inhibitory basal ganglia output in the Parkinsonian state is thought to decrease activity in the thalamus (Albin et al 1989;DeLong 1990;Galvan et al 2015). Similar decreases in firing rates were found in several previous studies, including Parkinsonian patients (Chen et al 2010;Molnar et al 2005), MPTP-treated cats (Schneider and Rothblat 1996), and 6-hydroxydopamine (6-OHDA)-lesioned rats (Ni et al 2000). However, other studies found either no change in thalamic firing activity in MPTP-treated monkeys (Pessiglione et al 2005) or increases in firing in 6-OHDA-treated rats (Bosch-Bouju et al 2014).…”
Section: Mptp-induced Changes Of Thalamic Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the classical model of the functional basal ganglia circuitry, in which increased inhibitory basal ganglia output in the Parkinsonian state is thought to decrease activity in the thalamus (Albin et al 1989;DeLong 1990;Galvan et al 2015). Similar decreases in firing rates were found in several previous studies, including Parkinsonian patients (Chen et al 2010;Molnar et al 2005), MPTP-treated cats (Schneider and Rothblat 1996), and 6-hydroxydopamine (6-OHDA)-lesioned rats (Ni et al 2000). However, other studies found either no change in thalamic firing activity in MPTP-treated monkeys (Pessiglione et al 2005) or increases in firing in 6-OHDA-treated rats (Bosch-Bouju et al 2014).…”
Section: Mptp-induced Changes Of Thalamic Activitysupporting
confidence: 91%
“…Increases in bursting were described previously in the motor thalamus of MPTP-treated monkeys (Guehl et al 2003;Pessiglione et al 2005). A similarly high incidence of burst firing has been found in corresponding areas in Parkinson's disease patients (Magnin et al 2000;Molnar et al 2005;Zirh et al 1998). Interestingly, in Parkinsonian monkeys, Pessiglione et al (2005) found that burst activity increased in both basal ganglia and cerebellar territories but that this reached significance only in the cerebellar-receiving area of the thalamus.…”
Section: Mptp-induced Changes Of Thalamic Activitysupporting
confidence: 64%
“…These findings also suggest that effective high-frequency DBS opposes the effects of essential tremor by overriding oscillatory bursts and irregular activity in the thalamus. There is an increase in bursting, irregular activity, and in the overall rate of activity in the Vim thalamus of subjects with essential tremor compared with subjects without essential tremor (Molnar et al 2005a). We previously found that changes in model neuron response variability as a function of frequency matched remarkably well the changes in tremor as a function of frequency (Grill et al 2004), and suggested that the function of high-frequency DBS is to override pathological activity.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on single unit recordings from NHPs and PD patients have shown that different subtypes of pyramidal, thalamocortical, and pallidal neurons may have different patterns under PD conditions and DBS (76,79,(90)(91)(92), and MSNs in the striatum may respond differently to the loss of dopamine depending on the prominent expression of D 1 or D 2 receptors (68). Our model focused on small neural populations with homogeneous properties and reproduced only a subset of the multifarious effects of Parkinson's disease and DBS.…”
Section: Discussionmentioning
confidence: 99%